Novel Targets for Anti-Inflammatory Therapy in Inflammatory Bowel Disease - John L Wallace (Canadian Journal of Gastroenterology)
Until the cause(s) of inflammatory bowel disease are identified, improvements in therapy will likely come from improved anti-inflammatory therapy or improved drug delivery systems. There are many potential targets for anti-inflammatory therapy, including the synthesis of specific inflammatory mediators. This review focuses on the potential for developing therapy aimed at three targets: nerves and neuropeptides; coagulation and thrombosis; and adhesion molecules. In each case, evidence is presented from clinical and/or experimental studies that supports the hypothesis that these are rational targets for anti-inflammatory drug development.